Option A:
![g(x) =x^4+x^3-7x^2-x+6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/w4hi2mv4gy1vr85gixzj4ftymzzo8qmj7p.png)
Solution:
Given data: Zeroes are 1, 2, –3, and –1.
To find the polynomial of the function for the given zeroes.
If 1 is a root of the polynomial then the factor is (x – 1).
If 2 is a root of the polynomial then the factor is (x – 2).
If –3 is a root of the polynomial then the factor is (x – (–3)) = (x + 3).
If –1 is a root of the polynomial then the factor is (x – (–1)) = (x + 1).
On multiplying the factors, we get the polynomial of the function.
![\Rightarrow\ g(x)=(x-1)(x-2)(x+3)(x+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/73kpb5p5dnviyjxmbfggqy8dzqh5adns9o.png)
![\Rightarrow\ \ \ \ \ \ \ \ =(x^2-2x-x+2)(x^2+x+3x+3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hiqmoqu2fp3lehkclqbr5j5eux15xai2f0.png)
![\Rightarrow\ \ \ \ \ \ \ \ =(x^2-3x+2)(x^2+4x+3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/n0ef47ee5x50w9no8soq2ufqemb01vh6gm.png)
Now multiplying each term of the first factor by each term of the second.
![\Rightarrow\ \ \ \ \ \ \ \ =x^2(x^2+4x+3)-3x(x^2+4x+3)+2(x^2+4x+3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wj9rmr30wyl54qx9axwsaoayn4q14d73i6.png)
![\Rightarrow\ \ \ \ \ \ \ \ =(x^4+4x^3+3x^2)+(-3x^3-12x^2-9x)+(2x^2+8x+6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/z2vb7l8pv5v0n5gtejcasjhanb5ypsi2kw.png)
Removing brackets in each term.
![\Rightarrow\ \ \ \ \ \ \ \ =x^4+4x^3+3x^2-3x^3-12x^2-9x+2x^2+8x+6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p5xa6xze9lgcypq1fk06zkusr1pthmnqrn.png)
Combine the like terms and simplifying.
![\Rightarrow\ \ \ \ \ \ \ \ =x^4+4x^3-3x^3+3x^2-12x^2+2x^2-9x+8x+6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2zf699v11klonm0zcvyuagpij124glbumq.png)
![\Rightarrow\ \ \ \ \ \ \ \ =x^4+x^3-7x^2-x+6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h8xxvqxbcjchgfz5vb2hwed32dr1r2wtb2.png)
![\Rightarrow \ g(x) =x^4+x^3-7x^2-x+6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/byoygybrk7h0bms082tm6hcys705fxkwss.png)
Option A is the correct answer.
Hence
.